PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT POS INDONESIA CABANG TANGERANG - Futuh Al Arifin; Didi Sunardi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the effect of Leadership and Work Discipline on Employee Performance at PT Pos Indonesia Tangerang Branch. The research method used is quantitative with an associative approach. The saturated sampling technique in this study is all employees of PT Pos Indonesia Branch, totaling 72 employees. The results of the study based on the t test show that Leadership (X1) has a significant influence on Employee Performance (Y) with a t-count value of 9.570> 1.666 (t table) with Sig. 0.000 <0.05. Work Discipline (X2) also has a significant influence on Employee Performance (Y) with a t-count value of 8.232> 1.666 (t table) with sig. 0.000 <0.05. Furthermore, the F test shows that simultaneously Leadership (X1) and Work Discipline (X2) have a significant effect on Employee Performance with an F-count value of 220.217> 2.74 (F table) with a sig. 0.000 < 0.05. Thus, both variables jointly contribute to improving employee performance. The resulting coefficient of determination is 0.865 x 100% = 86.5%. This means that the Leadership and Work Discipline variables contribute 85.5% to improving employee performance, while the remaining 13.5% was not examined in this study.